Since you have the answers, I'll just show the steps on how to get there.
============================================================
Problem 19
![(1+4i)^2\\\\(1+4i)(1+4i)\\\\1*1 + 1*4i + 4i*1 + 4i*4i\\\\1 + 4i + 4i + 16i^2\\\\1 + 4i + 4i + 16(-1)\\\\1 + 4i + 4i-16\\\\(1-16) + (4i+4i)\\\\(1-16) + (4+4)i\\\\-15 + 8i\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/94ic3n503pa88qqfvag3n8bsp9nfhiblla.png)
Keep in mind that
by definition. Squaring both sides leads to
![i^2 = -1](https://img.qammunity.org/2022/formulas/mathematics/college/sl8n1f0o6jy2mc46njcru4dbvcxhlow3a6.png)
In the second step, I used the idea that x^2 = x*x. Right after that, I used the FOIL rule to expand everything out.
============================================================
Problem 21
We could follow the same idea as problem 19, but I'll use a different approach.
![(A+B)^2 = A^2+2AB+B^2\\\\(3+i)^2 = 3^2 + 2*3*i + i^2\\\\(3+i)^2 = 9 + 6i - 1\\\\(3+i)^2 = 8 + 6i\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/htxfvb02vahos54ergjvpnrqqc5q1kyh8g.png)
The formula on the first line is the perfect square binomial formula.
============================================================
Problem 23
The FOIL rule can be used if you want, but I'll use the difference of squares rule instead.
![(m+n)(m-n) = m^2 - n^2\\\\(3+5i)(3-5i) = (3)^2 - (5i)^2\\\\(3+5i)(3-5i) = 9 - 25i^2\\\\(3+5i)(3-5i) = 9 - 25(-1)\\\\(3+5i)(3-5i) = 9 + 25\\\\(3+5i)(3-5i) = 34\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/ap2m0b8l7rnkvim304yuv4ht12omqf3gtq.png)
It turns out that multiplying any complex number of the form a+bi with its conjugate a-bi will result in a purely real number (that has no imaginary part). More specifically:
![(a+bi)(a-bi) = a^2+b^2](https://img.qammunity.org/2022/formulas/mathematics/college/8n9dnp8htdgz9ke901cwzp69kni2k11lfj.png)
============================================================
Problem 25
We could use the difference of squares rule again, but I'll show a different approach. This time using the distribution rule. The FOIL rule could also be used if you wanted.
![(6+7i)(6-7i)\\\\x(6-7i)\\\\6x-7xi\\\\6(x)-7i(x)\\\\6(6+7i)-7i(6+7i)\\\\6(6)+6(7i)-7i(6)-7i(7i)\\\\36+42i-42i-49i^2\\\\36-49(-1)\\\\36+49\\\\85\\\\](https://img.qammunity.org/2022/formulas/mathematics/college/505xr1fbo3e76m7d8c876m69rh9z0fb4hv.png)
I used x = 6+7i and the substitution property to help distribute. Lines 3 and 6 are where distribution is applied.